2003
DOI: 10.4319/lo.2003.48.5.1825
|View full text |Cite
|
Sign up to set email alerts
|

The role of the picoeukaryote Aureococcus anophagefferens in cycling of marine high—molecular weight dissolved organic nitrogen

Abstract: Environmental evidence suggests that Aureococcus anophagefferens (Pelagophyceae), a eukaryotic picoplankton that blooms in coastal seawaters, can outcompete other organisms because of its ability to use abundant dissolved organic nitrogen (DON). To test this hypothesis, we isolated A. anophagefferens in axenic culture and monitored its growth on high-molecular weight (HMW) DON collected from sediment pore waters, a putative source for DON in bays where blooms occur. HMW DON originating from pore water had a su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 30 publications
2
33
0
Order By: Relevance
“…Studies have shown that, especially during summer when nutrients are depleted, DOM can be an important nutrient fuelling primary production (Berg et al, 2003;Korth et al, 2011;Stepanauskas et al, 1999), and especially for sensible ecosystems like the Baltic Sea terrestrial DOM inputs are assumed to strongly influence the biogeochemistry.…”
Section: B Deutsch Et Al: Inputs Of Terrestrial High Molecular Weightmentioning
confidence: 99%
“…Studies have shown that, especially during summer when nutrients are depleted, DOM can be an important nutrient fuelling primary production (Berg et al, 2003;Korth et al, 2011;Stepanauskas et al, 1999), and especially for sensible ecosystems like the Baltic Sea terrestrial DOM inputs are assumed to strongly influence the biogeochemistry.…”
Section: B Deutsch Et Al: Inputs Of Terrestrial High Molecular Weightmentioning
confidence: 99%
“…It is likely that these enzymes are capable of cleaving the N from a wide range of additional DON compounds allowing phytoplankton to, in effect, "farm" N from these compounds while leaving the remainder of the compound external to the cell (Mulholland et al, 1998;Berg et al, 2003b;Stoecker and Gustafson, 2003).…”
Section: Enzymatic Breakdownmentioning
confidence: 99%
“…Unlike many co-occurring microalgal species, Aureococcus anophagefferens has qualities consistent with phytoplankton adapted to a more oligotrophic, deep-water environment, such as relatively sensitive functional responses to reduced nitrogenous nutrients (NH 4 + , glutamate, and urea) and relatively low light requirements (Dzurica et al 1989, Yentsch et al 1989, Lomas et al 1996, Milligan & Cosper 1997. While photoautotrophic and capable of growing solely on inorganic nutrients, A. anophagefferens also appears adept at utilizing a variety of dissolved organic nutrients, including proteins, which qualifies it as a mixotroph (Dzurica et al 1989, Lomas et al 1996, Berg et al 1997, 2003b, Mulholland et al 2002. Despite A. anophagefferens' rather modest growth potentials (μ max ≤ 0.80 d -1 ), its unique combination of attributes may provide competitive advantages over other species and permit the occupation of a turbid niche dominated by reduced nitrogen species.…”
Section: Algal Responses To N-speciationmentioning
confidence: 99%
“…All results reported above are consistent with the hypothesis that moderate effluxes of reduced N from sediments favor BT proliferation in Long Island estuaries over blooms of competing phytoplankters (LaRoche et al 1997, Gobler & Sañudo-Wilhelmy 2001a). In addition to reduced nitrogen, A. anophagefferens growth may also be stimulated by organic carbon enrichments provided by porewater amendments (Burdige & Homstead 1994, Lomas et al 1996, Berg et al 1997, 2003b.…”
Section: Field Validationmentioning
confidence: 99%